Função sistólica do ventrículo esquerdo em cães com doença mixomatosa valvar mitral - Sousa, Paulo Roberto de (2019)
Myxomatous mitral valve disease (MMVD), or mitral valve endocardiosis, is the most prevalent acquired heart disease in dogs, being the main cause of heart failure in small dogs. The echocardiographic examination, which allows cardiac morphological and functional evaluation, is considered the “gold standard” test for diagnosing and staging MMVD in dogs. Information obtained by echocardiography on ventricular function also determines the prognosis in dogs with MMVD, since systolic dysfunction is a risk factor in these patients and contributes to the development of heart failure. However, the assessment of ventricular systolic function using conventional echocardiographic indexes is limited, since it is directly influenced by preload and afterload factors. The evaluation of cardiac mechanics by strain (ST) and strain rate (STR), using two-dimensional speckle tracking (2D-STE), allows, in humans, an earlier diagnosis of ventricular dysfunction. In addition, the mitral ring tissue displacement (TMAD) is an index of longitudinal systolic function that has a good correlation with conventional echocardiographic indices and low intra and interobserver variability. Thus, the objective of this study was to verify whether the myocardial deformity indexes (ST and STR) and the TMAD are more accurate and precocious than the conventional echocardiographic indexes in the assessment of left ventricular systolic function in dogs with MMVD, measuring the variables in the day of diagnosis (T0) and after 30 days (T30). For this purpose, 29 dogs were evaluated, categorized according to the ACVIM consensus, eight of which were in stage B1, 12 in stage B2 and nine in stage C. Considering the conventional variables used in this study, the presence of systolic dysfunction was not observed in dogs with MMVD, however changes after the start of pharmacological treatment were observed in the variables FET% and MAM. From the 2D-STE evaluation, similar to the conventional evaluation, systolic dysfunction cannot be determined in dogs with MMVD. However, the longitudinal ST variable indexed by weight showed a significant increase between the assessment times in group C, being still significantly higher in C than in B2, at administration, and higher in C than in the other groups after treatment. For the variable longitudinal STR it decreased in T30 in B1 and increased in C. When comparing the groups, in T30, group C showed higher values than in B1 and B2. Still, the variables longitudinal ST and TMAD showed a significant negative correlation when indexed to weight. In conclusion, the assessment of myocardial deformity using 2D-STE assessment did not demonstrate superiority compared to conventional indices for the diagnosis of systolic dysfunction in dogs with MMVD in its different stages.